Efektivitas Rhizobium sp, Mikoriza dan Pupuk Kandang Terhadap Pertumbuhan Tanaman Kedelai di Tanah Masam: The Effectiveness of Rhizobium sp Inoculation, Mycorrhiza, and Manure Fertilizer Dosage on the Growth of Soybean Plants (Glecine max (L.) Meril) in Acidic Soil - Muh. Arfandy Wiranata; Muh Jayadi (Jurnal Ecosolum, 2026)
Indonesia has extensive marginal land resources, one of which is acidic dry land covering approximately ±102.8 million hectares. This land type poses a major constraint to soybean development due to low nutrient availability and high aluminum saturation. One approach to overcoming the limitations of acidic soils is the use of biofertilizers such as Rhizobium sp. and mycorrhizae to enhance phosphorus availability, combined with the application of organic amendments in the form of chicken manure, which is rich in potassium and phosphorus. This study aimed to determine the optimal combination of chicken manure dosage and inoculation of Rhizobium sp. and mycorrhizae for improving soybean growth on acidic soils. The experiment was arranged in a factorial Randomized Complete Block Design (RCBD) with two factors and three replications, resulting in 36 treatment combinations. The first factor was the dosage of chicken manure: A0 (without chicken manure), A1 (1 ton ha⁻¹), and A2 (2 tons ha⁻¹). The second factor was microbial inoculation, consisting of R0M0 (without inoculation), R1 (Rhizobium sp.), M1 (mycorrhizae), and R1M1 (combined Rhizobium sp. and mycorrhizae). Observed parameters included soil chemical properties and soybean growth components. The results showed that the A2R1M1 treatment (2 tons ha⁻¹ chicken manure + Rhizobium sp. + mycorrhizae) produced the best outcomes in soil chemical properties, as indicated by increased cation exchange capacity (17.97 cmol kg⁻¹), available phosphorus (9.02 ppm), and total nitrogen (0.23%), along with reduced exchangeable aluminum (0.32). This treatment also resulted in superior plant growth, reflected by increased plant height (91.0 cm), number of leaves (41.3 leaves), fresh weight (13.05 g), dry weight (4.14 g), and number of pods (8.7 pods). The combination of chicken manure, Rhizobium sp., and mycorrhizae was proven effective in improving acidic soil chemical properties and enhancing soybean growth.